Information Seeking Upon Exposure to Risk Messages: Predictors, Outcomes, and Mediating Roles of Health Information Seeking. (July 2019) - So, Jiyeon; Kuang, Kai; Cho, Hyunyi
Exposure to risk messages can motivate health information seeking, which can influence message acceptance or rejection. Theories of risk message design and effects (e.g., fear appeal models), however, have not considered information seeking as an integral part of the risk message processing. To address the gap, this experimental study ( N = 927) offered participants an opportunity to seek threat- and/or coping-related information online after exposing them to a risk message about meningitis and recorded their information seeking activities unobtrusively. The findings indicated that information seeking increased self- and response-efficacy of meningitis vaccination. Information seeking was positively predicted by uncertainty discrepancy, perceived susceptibility, anxiety, and fear. More importantly, information seeking completely mediated the effects of perceived susceptibility and anxiety on an increase in self- and response-efficacy, and a decrease in message rejection. Information seeking also partially mediated the effects of perceived susceptibility and fear on an increase in message acceptance. Implications for health information seeking and risk communication research are discussed.